Impact of Thermally Activated Building Systems (TABS) in Office Buildings - Kgaladi, Lebogang (Department of Mechanical Engineering, 2024)
Thermal comfort can be described as the degree to which a person is satisfied with their thermal environment (Yau & Chew, 2014). It is a person's perception of whether they feel warm or cool within their surroundings. The Danish professor, Povl Ole Fanger, developed the Predictive Mean Vote (PMV), a model consisting of physical and personal variables to quantify a person's thermal comfort within a building. The physical variables include air temperature, relative humidity, mean radiant temperature, and air velocity, and the personal variables include activity level and clothing insulation (Yau & Chew, 2014). People control the physical variables using systems that provide heating and cooling to an environment, the earliest of which were found in 9 000-year-old remains from Eastern Turkey (Ma, Wang, & Guo, 2015). The remains consisted of an intermediate space beneath the floor that would have been filled with cold water from Kantara Creek to cool the interior during warm seasons. Personal variables are controlled by changing the individual's activities and clothes. Today there are various space heating and cooling systems implemented in buildings. This research describes Thermally Activated Building Systems (TABS) and conventional Heating, Ventilation and Air-conditioning (HVAC) systems. Both systems consist of components such as the boiler, chiller and heat pump to condition the fluid used to deliver the heating and cooling. The systems differ and are classified by their heating and cooling transfer processes within the building's interior. HVAC systems use the air to transfer heat by convection, and TABS use the buildings' internal surfaces to transfer heat by radiation (Rhee, Olesen, & Kim, 2012). HVAC systems include Air Handling Units (AHUs) to deliver the conditioned air and provide dehumidification. In contrast, TABS consists of conditioned water pumped through pipes embedded within the building's floor, walls, and ceilings to transfer heat between internal wall surfaces. The combination of water and building material has a higher thermal capacity than air, making TABS more energy-efficient at transferring heat than HVAC systems. This research presents case studies to determine the magnitude by which TABS is more energy-efficient by analysing and comparing both systems' energy consumption as they deliver thermal comfort. The first case study consisted of an office building located in Cape Town, South Africa, with a TABS installation. The pipe layout in the building's floors was designed and optimised using LoopCAD for its construction between November 2018 and September 2020. The office building was modelled, and the heat load was simulated in EnergyPlus to determine the cooling needed to achieve thermal comfort. The cooling required was used as input into a modified TABS calculator, derived from the calculator given in ISO 11855, to predict the energy usage of the chiller. The electricity consumption determined by the TABS calculator was consistent with the actual chiller's electricity consumption. The mean difference between actual and calculated results is 2.054. It was determined that the TABS calculator results have an 80% confidence level to be within 1.17 of the actual chiller demand. A PMV calculator, rewritten from the calculator given in ISO 7730 and ASHRAE-55, was used to predict the thermal comfort of the occupants in the building. The calculator was tested, and its results were compared with the standard's. It was determined that the calculator's PMV and PPD results have an 80% confidence level to be within 0.015 and 0.5, respectively, of the ISO 7730 calculator's results. The calculator used the results from the TABS calculator to determine that the occupants were likely satisfied with their thermal environment. The second case study consisted of an office building similar to the first case study, located in Cape Town, South Africa, except with a conventional HVAC installation. Its HVAC system was optimised by installing Variable Speed Drives (VSDs) at the pumps and fans. A simplified building model was developed in SketchUp Pro and imported into EnergyPlus to model and simulate the HVAC system. As with the first case study, the chiller's energy consumption determined by the simulation was consistent with the actual chiller energy consumption. It was determined that EnergyPlus results have an 80% confidence level to be within 0.57 of the actual chiller demand. The simulation also determined that the occupants were likely satisfied with their thermal environment. The case studies showed that the TABS calculator and EnergyPlus could accurately simulate the energy usage of TABS and conventional HVAC systems. The buildings in which the systems were installed had different cooling loads, occupancy levels and thermal insulation making it challenging to compare the systems. Therefore, the systems were modelled and simulated in the same building to prove the research hypothesis. The third case study, involving a simple office building, was modelled in SketchUp Pro and imported into EnergyPlus. As with the first case study, the cooling load determined from EnergyPlus simulations were used as inputs into the TABS calculator to determine the energy consumption of the chiller. A Variable Air Volume (VAV) HVAC system was modelled on the building, and the chiller energy consumption was simulated. When comparing the sensible energy consumption of both systems, the simulations show that TABS consumes 41.62% of the HVAC chiller's energy to provide the same neutral thermal experience. TABS' reduced energy consumption presented an opportunity for a business case of installing the system into an Eskom building with an HVAC system that had reached its end of life. The installed HVAC system used in the business case consumed 8 056 961 kWh annually and, using Eskom's 2018/19 electricity tariff, cost R5 858 518 to operate. Using an annual tariff increase of 6% (the South African Reserve Bank's maximum CPI target) and Eskom's discount rate of 10.4%, the business case resulted in the following options: 1. Replace the HVAC system with an energy-efficient HVAC system would cost R20 360 000 to install, consume 4 212 129 kWh annually and cost R3 062 797 to operate in the initial year. Compared to the current HVAC installation, the proposed installation would have a simple payback period of seven years and a discounted payback of ten years. 2. Install a more expensive TABS installation at a proposed cost of R29 581 440. Although installing TABS costs more than an energy-efficient HVAC system, the TABS would consume less electricity and cost less to operate. The system was estimated to consume 2 384 908 kWh annually and cost R 1 734 156 to operate in the initial year. Similar to the HVAC option, the TABS installation would have a simple payback period of seven years and a discounted payback of ten years. At first glance, it seems that there is no business case to opt for the TABS instead of the HVAC installation. However, the average increase in the electricity tariff has been 12.17% annually for Eskom's 2019/20 and 2020/21 financial years. The average tariff increase gives the TABS installation a simple and discounted payback period of 7 and 12 years, while the replacement HVAC system has a simple payback period of 9 years and no discounted payback period. TABS also has the added advantages of a consistent temperature gradient and mitigating cold draughts resulting from excessive air movements (Rhee, Olesen, & Kim, 2012)